Plan de mejoramiento para el proceso operativo de fletamentos de los buques que arriban a los puertos marítimos de santa marta (2023)
This work contains the development of an improvement plan for the charter operational process in the General Maritime Directorate DIMAR, through which the arrival of ships and boats in the port captaincy of Santa Marta is executed. In order to improve this procedure and update it, we seek to understand how it is currently carried out in the entity, therefore, data collection was carried out through a survey to find points of improvement and optimization to streamline the process and make it efficient. In the course of this work, the importance of DIMAR in all Colombian foreign trade activities and its work as a regulatory body for seaports is exposed, as well as its contribution to the development of the country's maritime sector. Since its creation, DIMAR has been an entity in charge of promoting the activities of the Colombian maritime sector and regulating international trade activities within its function as a coordinating entity for maritime ports. Likewise, it is the entity that is responsible for giving due compliance to the policies or regulations adopted by Colombia from the International Maritime Organization (IMO), such as the code for the protection of ships and port facilities ISPS, which plays a role. important role in the regulatory regime of international maritime transport.To execute the above, the DIMAR makes available to the Customs Agencies and Shipping Companies the issuance of charters for the arrival of vessels that import and market merchandise in the country, which can be a complex process, if not carried out. carried out correctly, as is currently the case that these companies have presented problems when issuing the corresponding document, this being an opportunity to improve the activities of this entity and continue contributing to the development of the country's international trade.To prepare this improvement plan within the entity, it was necessary to carry out data collection activities, so a schedule of activities was proposed where the steps to follow were established to carry out the review of information about the process and the investigation of how is executed in the entity, as well as the implementation of improvement alternatives in the DIMAR This initiative seeks to promote support for small investigations and analysis that include the evaluation of processes in order to measure their performance taking into account the current process, which is established in the entity's regulations and carried out in all its port captaincies, since DIMAR as a Colombian maritime authority has jurisdiction throughout the national maritime jurisdiction.